2022
DOI: 10.3390/antiox11061210
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Responsive Gel Containing Hydroxytyrosol-Chitosan Nanoparticles (Hyt@tgel) Counteracts the Increase of Osteoarthritis Biomarkers in Human Chondrocytes

Abstract: Although osteoarthritis (OA) is a chronic inflammatory degenerative disease affecting millions of people worldwide, the current therapies are limited to palliative care and do not eliminate the necessity of surgical intervention in the most severe cases. Several dietary and nutraceutical factors, such as hydroxytyrosol (Hyt), have demonstrated beneficial effects in the prevention or treatment of OA both in vitro and in animal models. However, the therapeutic application of Hyt is limited due to its poor bioava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…The DPPH assay results indirectly prove the efficiency of the M-Ext against aging and oxidative stresses due to the presence of TPC and TFC. Outcomes based on DPPH activity of M-Ext, M-Ext is suitable as an antiaging or antioxidative stress agent in pharmaceutical or pharmaceutical formulations [ 14 , 53 ]. Therefore, it could be a new approach to formulate green formulation to cope with early aging and oxidative stresses that results in thwarted life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DPPH assay results indirectly prove the efficiency of the M-Ext against aging and oxidative stresses due to the presence of TPC and TFC. Outcomes based on DPPH activity of M-Ext, M-Ext is suitable as an antiaging or antioxidative stress agent in pharmaceutical or pharmaceutical formulations [ 14 , 53 ]. Therefore, it could be a new approach to formulate green formulation to cope with early aging and oxidative stresses that results in thwarted life.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have good potency to control the overproduction of FRs [ 10 ]. M. indica crude extract (peels and kernel) showed tyrosinase inhibition [ 11 , 12 ] and reversible inhibition of elastase and collagenase enzymes [ 13 ], which makes it appropriate for use in pharmaceutical and cosmetic products to treat dermatitis, psoriasis, acne, and premature skin aging [ 14 ]. The topical application of M. indica kernel extract is limited due to its low shelf life, poor solubility, and low skin permeation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels and nanoparticles were combined to develop a drug delivery platform of hydroxytyrosol, composed of hyaluronic acid and Pluronic F127. On injection, the thermosensitive formulation underwent a sol–gel transition at body temperature with resultant sustained action [ 92 ].…”
Section: Thermosensitive In Situ Gels Loaded With Micro and Nanoparti...mentioning
confidence: 99%
“…The smart hydrogel was further used to encapsulate hydroxytyrosol-loaded chitosan nanoparticles for the treatment of osteoarthritis. The in vitro study demonstrated that the combination of hydrogels and antioxidant-loaded nanoparticles showed potential use in the treatment of the chronic inflammatory degenerative disease [ 18 ].…”
mentioning
confidence: 99%